Some New and Noteworthy Diseases of Poplars in India - Singh, Sujan; Khan, S. N.; Misra, B. M. (Indian Forester, 1983)
Four new diseases of poplars namely Botryodiplodia sett-rot, Altremaria tip hlight. Cladosporium leaf spot and Fusarium pink incrustation are described in this paper. Botryodiplodia paimarum causes sett-rot of poplars both at pre-sprouting and post-sprouting stage The pathogen also causes mortality of poplar plants in the field within 4-6 weeks alter planting. Alternaria stage of Pleospara infectoria has been found as the cause of blackening and dying of growing tips and young leaves of a Populus sp. & P. deltoides in nurseries. Cladosporium hlumile has been recorded as the cause of brown spot followed by crumpling and premature of shedling of leaves in P. ciliata. P. nigra and P. alha. The cause of Fusarium incruatation disease on P. ciliata bas been identified as Fusarium sp. of Gibbosum group Pathogenicity of Batryodiplodia palmaram & Ailernaria stage of Pleospora infectoria was confirmed by artificial inoculations. Brief descriptions of Ailernaria. Cladosporium & Fusarium are also given. The paper also gives a short account of some noteworthy diseases recorded on poplars namely Ganoderma root rot, foliage rusts and stem cankers. Ganoderma root-rot is found to reach alarming proporthlns in closely spaced poplar plantations. Melampsora Ciliata, an indigenous fust, is found to attack many clones of P deltoides, P. yunnannensis, P. trichocarpa, P. alba and some cultivars of P. x euramericana in nurseries. A brief account of three types of stem cankers i.e.can kers due to pink disease fungus, Corticium salmonicolor. Sun-scald cankers and cankers associated with slime flux on various clones of of P. deltoides is also given.